1954
DOI: 10.1136/bmj.2.4879.73
|View full text |Cite
|
Sign up to set email alerts
|

Gas Transport Function of the Blood in Congenital Familial Methaemoglobinaemia

Abstract: BODY WEIGHT AFTER GASTRECTOMY MED] previously were much over standard weight. Different patterns of post-operative weight loss are discussed. Defective fat absorption follows gastrectomy, but the significance of this alone in relation to body weight is doubtful. Both dietary calorie intake and fat absorption are related to body weight, and failure to gain is greatest when both are impaired.When loss of weight follows operation it occurs in the first few post-operative weeks, and thereafter the patient cann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1956
1956
1982
1982

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…An increased mechanical fragility of the circulating corpuscles through contact with plasma lead was regarded as the essential feature of the anaemia of lead poisoning. Indirect evidence which supported this view has been reported more recently, namely, raised urobilinogen excretion in lead-poisoned guinea-pigs (Baikie, 1954) and coproporphyrinuria I in severely poisoned workmen (Kench, Lane, and Varley, 1952). The data in a recent investigation (Holecek and Penickova', 1957) are unfortunately qualitative only.…”
mentioning
confidence: 86%
“…An increased mechanical fragility of the circulating corpuscles through contact with plasma lead was regarded as the essential feature of the anaemia of lead poisoning. Indirect evidence which supported this view has been reported more recently, namely, raised urobilinogen excretion in lead-poisoned guinea-pigs (Baikie, 1954) and coproporphyrinuria I in severely poisoned workmen (Kench, Lane, and Varley, 1952). The data in a recent investigation (Holecek and Penickova', 1957) are unfortunately qualitative only.…”
mentioning
confidence: 86%
“…In two cases of congenital familial methemoglobinemia Baikie and V altes (27) found that the oxygen dissociation curve of their patients became normal following methylene blue adActa hacmat., Vol. 37, No.…”
Section: Discussionmentioning
confidence: 99%